Thomas Lickona's Concept of Character Education in the Perspective of Educational Management - Rizky, Mochammad; Istikomah, Istikomah; Huda, Miftahul (JURNAL AL-TANZIM, 2026)
The transformation of education in the Society 5.0 era requires educational systems that adapt to rapid technological advancement while strengthening students’ character development. However, studies on Thomas Lickona’s character education have primarily focused on classroom-level pedagogy, leaving its relevance in educational management underexplored. This study aims to analyse the integration of Lickona’s character education framework into educational management in the context of Society 5.0. Using a Systematic Literature Review (SLR), ten peer-reviewed articles published between 2020 and 2025 were analysed through identification, screening, eligibility, and thematic synthesis stages. The findings reveal three dominant patterns. First, curriculum integration embeds moral knowing, moral feeling, and moral action into learning Design to support ethical reflection. Second, strengthening school culture emphasises institutional values, leadership modelling, and habitual practices in sustaining moral behaviour. Third, technology-supported character learning shows that digital media enhance moral engagement when guided by ethical management. Overall, character education is more effective when implemented systemically at the managerial level. This study contributes by repositioning Lickona’s framework as a management-oriented paradigm for human-centred education. Future research should expand empirical validation and explore AI-supported models of character education.